2021
DOI: 10.1007/s43440-020-00209-9
|View full text |Cite
|
Sign up to set email alerts
|

1MeTIQ and olanzapine, despite their neurochemical impact, did not ameliorate performance in fear conditioning and social interaction tests in an MK-801 rat model of schizophrenia

Abstract: Background The aim of the present study was to evaluate the effect of 1MeTIQ on fear memory and social interaction in an MK-801-induced model of schizophrenia. The results obtained after administration of 1MeTIQ were compared with those obtained with olanzapine, an antipsychotic drug. Methods Sprague–Dawley rats received a single injection of MK-801 to induce behavioral disorders. 1MeTIQ was given either acutely in a single dose or chronically for 7 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
(75 reference statements)
1
2
0
1
Order By: Relevance
“…One rat study, for instance, found that aripiprazole administered at lower doses than those used in our study could reverse the social interaction deficit induced by an acute administration of MK-801 [59]. On the other hand, other studies found that aripiprazole used at comparable doses as well as other atypical antipsychotics such as olanzapine, risperidone and clozapine had no effect on the social deficit provoked by MK-801 or PCP [32,[60][61][62], which perfectly aligns with our results. Hence, it is possible that the lack of effect of aripiprazole was either because the dose tested was too strong or because it was not able to produce an effect on the root cause of social dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…One rat study, for instance, found that aripiprazole administered at lower doses than those used in our study could reverse the social interaction deficit induced by an acute administration of MK-801 [59]. On the other hand, other studies found that aripiprazole used at comparable doses as well as other atypical antipsychotics such as olanzapine, risperidone and clozapine had no effect on the social deficit provoked by MK-801 or PCP [32,[60][61][62], which perfectly aligns with our results. Hence, it is possible that the lack of effect of aripiprazole was either because the dose tested was too strong or because it was not able to produce an effect on the root cause of social dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Behavioral tests were performed and analyzed using a computer-controlled FC system (TSE, Bad Homburg, Germany) as described previously by Chocyk et al [ 38 ] and Bialon et al [ 51 ]. Each FC unit consisted of sound-attenuating housing with a loudspeaker, camera, ventilation fan and 4 symmetrically mounted lamps in the ceiling construction and test box.…”
Section: Methodsmentioning
confidence: 99%
“…MK-801 is commonly used in mice and rats [ 98 , 99 ]; however, it is less often found in zebrafish [ 100 ] and monkey [ 101 ] studies. In rodents, the behavioral effects of MK-801 include working perturbations [ 102 , 103 ], hyperlocomotion [ 103 , 104 ], deficits in PPI [ 102 , 104 ], lowered sociability [ 103 , 105 , 106 ], and fear conditioning perturbations [ 106 , 107 ]. Notably, the data presenting MK-801-induced anxiety behavior seem to be rather inconsistent; some studies show the anxiogenic effects of MK-801 administration [ 105 ], while other studies present undisturbed anxiety-related behavior [ 104 , 108 ].…”
Section: Pharmacological Modelsmentioning
confidence: 99%